Agrobacterium-mediated transformation of Nicotiana glauca and Nicotiana sylvestris - G. V. Khafizova; T. V. Matveeva (Вавиловский журнал генетики и селекции)
Agrobacterium-mediated transformation is the most popular approach for obtaining transgenic plants nowadays. There are plenty of protocols developed for different plant species. These protocols usually include the medium composition, the technology for preparing plant explants and cultivation conditions, as well as the choice of agrobacteria strains. Nicotiana tabacum, or cultivated tobacco, was one of the first successfully transformed plant species. Nicotiana tabacum is a model object in plant genetics, particularly due to its ability for transformation and regeneration. N. tabacum is a naturally transgenic plant since its genome contains a cellular T-DNA acquired from Agrobacteria. The significance of cT-DNA for plants has not yet been established. Some assume that cT-DNA can increase the ability of plants to regenerate due to some of the genes they contain. For example, rolC has been shown to affect the hormonal balance of plants, but the molecular mechanisms underlying this have yet to be found. RolC is also somehow involved in the secondary metabolism of plants. Like N. tabacum, Nicotiana glauca produces a wide range of secondary metabolites and contains an intact rolC gene in its genome. At the same time, unlike N. tabacum, N. glauca is a diploid species, which makes it more suitable for genetic engineering approaches. Nicotiana sylvestris is one of the ancestral species of N. tabacum and does not contain cT-DNA. The aim of this work was to develop a protocol for transformation and regeneration of N. glauca and N. sylvestris. We managed to find an optimum ratio of auxins and cytokinins that promotes both active callus formation and organogenesis in N. glauca and N. sylvestris leaf explants. The developed technique will be useful both for fundamental research that includes the N. glauca and N. sylvestris species, and for practical application in the pharmaceutical industry and biosynthesis.